An Analysis of Knowledge. Attitude. Family Support. and Compliances of Takipesial region of Yogyakartang Drugs Towards Diabetes Mellitus Type II in S (Public Health Perspective Journal, 2018)
Diabetes mellitus has quickly become one of the most common non-communicable diseases globally. According to the Health Centre Integrated Disease Surveillance Report of Yogyakarta Province in 2017 there were 8.321 cases of diabetes and the results showed that DM was the number 4 most common disease in DIY in 2017 with 152 deaths. The purpose of this study was to analyze knowledge.attitudes.family support.andcompliances of taking medication towards diabetes mellitus Type II in Sleman.Special Region of Yogyakarta. This research was a quantitative study with a cross sectional approach. The research sample consisted of 119 simple random sampling techniques. This research instrument used a questionnaire. The analysis in this study used Path Analysis. The results showed that there was a direct effect of knowledge on blood glucose levels with a path coefficient of 0.193 (p = 0.031 0.05). There is an influence of attitudes towards blood glucose levels with a path coefficient of 0.203 (p = 0.019 0.05). The community needs to adopt a healthy lifestyle. the health office and the local government need to conduct health education (KIE) in a comprehensive manner.